Economic Partership Agreeements and Regional Integration: A Case Study of the Southern Africa Customs Union and the Southern African Development Community - Mwanahawa, Aziza Khauhelo Mdee (Department of Public Law, 2014)
In many respects, developing countries have sought regional integration (RI) as the device to propel them into a new era of development and economic prosperity. Within an African context, the importance of regrouping countries was further strengthened by the need to deconstruct the artificial borders that had been imposed, and thus became a post-colonialism mantra. The belief in the importance of integration and its' consequent pursuit has continued, despite its admittedly limited success on the continent, amidst what has been referred to as a 'puzzling web of overlapping, contradictory and ineffective agreements. In this regard, Southern Africa is no exception. There is a litany of socio-economic challenges that the region faces. Consequently, regional organizations such as Southern African Development Community (SADC) and the Common Market for East and Southern Africa (COMESA) continue to search for new approaches to RI to enable them to tackle these challenges. Although technocrats profess 'integration fatigue', the advancement of regional efforts continues.